JAMINAN SOSIAL KESEHATAN: INTEGRASI PROGRAM JAMINAN KESEHATAN ACEH DALAM SISTEM JAMINAN SOSIAL NASIONAL - Mujibussalim Mujibussalim; Sanusi Sanusi; Fikri Fikri (Jurnal Dinamika Hukum, 2013)
This paper describes the authority of the Aceh Provincial Government in developing Aceh Health Social Security (AHSS) program within the context of Aceh special autonomy, and national social security system, and alternative models on procedure for collecting AHSS premium payment,  the readiness of  stakeholders in implementing the program. Methodology applied was by combining normative-legal research, comparative-legal research and socio-legal research.The finding shows that the Aceh government has authority to provide AHSS, which include providing health services and establishing a special local management body.  Model for premium collection can be combained of both insurance policy and central or local government contribution. Key Words: health social security, health social insurance, Aceh health social security